Welfare services and disabled children: Perspectives from parents in the municipality of Akureyri - Egilson, Snæfríður Þóra; Stefánsdóttir, Sara (Stjórnsýslustofnun, 2014)
The purpose of this study was to examine how parents of disabled children experience the services which they and their children receive from the family-service unit at the municipality of Akureyri, and to analyse factors relating to parents’ satisfaction with the services. This was a sequential mixed method study. Initially, the Measure of Processes of Care questionnaire was sent to parents of 115 disabled children, answering ratio was about 50%. Descriptive statistics, significance tests and correlation coefficients were used in the analysis. Subsequently 14 parents elaborated on the survey findings in focus groups interviews. Data analysis revealed that parents – particularly those with young children – found the services in line with family-centred values. Overall they experienced respectful and supportive attitudes, easy access to staff and that they provided important, flexible and relevant support. Nevertheless, a notable shortage of information was conveyed and that the responsibilities of the unit were somewhat unclear. Parents of children who need extensive daily support were more content than were parents of children who were mostly or fully independent. Parents of children with autism spectrum disorders were more discontent than parents of children with other types of impairments. Parents’ participation in decision-making and their positive experience of staff attitudes predicted their satisfaction with services. Thus special attention should be given to parental participation in decision-making and provision of information since lack of information may cause insecurity and experience of erratic services. Attention should be geared towards families of children in the upper grades of elementary school. Tilgangur rannsóknarinnar var að kanna reynslu foreldra fatlaðra barna af þjónustunni sem þeir og börn þeirra njóta hjá Fjölskyldudeild Akureyrarbæjar, og að greina þætti sem tengjast ánægju foreldra með þjónustuna. Notað var blandað skýringarsnið. Í upphafi var gögnum safnað með matslistanum Mat ...